Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1002/ajh.2830070307
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of fibrinolysis in diabetic children, mothers, and their newborn

Abstract: Late diabetic complications are often related to vascular changes and formation of thrombi in the altered vasculature. Contributing factors to thrombosis susceptibility of diabetic patients include changes in clotting factors, platelets, and inhibition of fibrinolysis. We have measured various fibrinolytic inhibitors in the blood of diabetic children, diabetic pregnant women and their offspring, and healthy controls. Inhibitors studied included 1) fast (immediate) antiplasmin, 2) slow (progressive) antiplasmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 45 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…To our knowledge, there are only a small number of studies evaluating α 2-anti-plasmin levels in Type 1 diabetes, although findings are consistent with our observations. In a recent study, the plasma plasmin- α 2-anti-plasmin complex (PAP) was associated with diabetic retinopathy and sight threatening diabetic retinopathy in Type 2 diabetics [10], and correlation was still significant after adjustments of the groups for age, gender, race, the study center, SBP, the use of diabetes medications, disease duration, HbA1c, and waist-to-hip ratio were made [25, 26]. A positive correlation between α 2-anti-plasmin with HbA1c suggests that fibrinolytic markers may improve with disease regulation and better glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are only a small number of studies evaluating α 2-anti-plasmin levels in Type 1 diabetes, although findings are consistent with our observations. In a recent study, the plasma plasmin- α 2-anti-plasmin complex (PAP) was associated with diabetic retinopathy and sight threatening diabetic retinopathy in Type 2 diabetics [10], and correlation was still significant after adjustments of the groups for age, gender, race, the study center, SBP, the use of diabetes medications, disease duration, HbA1c, and waist-to-hip ratio were made [25, 26]. A positive correlation between α 2-anti-plasmin with HbA1c suggests that fibrinolytic markers may improve with disease regulation and better glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific mechanism of increased thrombosis in IDM remains unclear, it is likely multifactorial with an interplay between genetic and environmental factors that lead to changes in the procoagulation, anticoagulation and thombolytic pathways. Various authors have reported increased proaggregatory platelet endoperoxide levels, decreased anti-aggregatory vascular prostacyclin levels (9), decreased plasminogen activity (6,7), protein C deficiency (10) and altered levels of fibrinolysis inhibitors, specifically increased fast antiplasmin and decreased slow antiplasmin levels (11). Compared with infants of nondiabetic mothers, thromboses in IDM were also reported to show more organization, calcification and earlier fatalities, with more than one-half of IDM expiring in utero, at birth or within the first 24 h of life (1,5).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of a2-macroglobulin in diabetic patients are reported to be high (Almer et al 1974;Ambrus et al 1979;James et al 1980) and to increase in parallel with the rise of HbAlc (Watzke et al 1988). The increase of plasma a 2-macroglobulin may delay correction of thickening of glomerular basement membrane by inhibiting of neutral protease activity and therefore inducing diabetic nephropathy (Brownlee 1976).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in diabetic patients, levels of a2-macroglobulin in blood increased irrespective of types of diabetes (Almer et al 1974;Ambrus et al 1979;James et al 1980). Furthermore, there is a positive correlation between plasm a2-macroglobulin levels and HbAlc (Watzke et al 1988).…”
mentioning
confidence: 96%
See 1 more Smart Citation